Evaluation of Conventional and Digital Broadcast Regulation: Challenges and Prospects in Nigeria - Olimma Benedette Ngozi; Michael A. Nzan-Ayang (International Journal of Sustainable Applied Sciences, 2023)
This paper tries to evaluate and ascertain the impact of the Nigerian broadcasting system on various broadcasting bodies, the researcher adopted the survey research method to get the sample size of 150 to represent the population of the study a total of 150 questionnaires were distributed to the respondents and 140 or (93.3%) were returned while 10 or (6.6%) questionnaires were not returned. The study findings reveal that the main methods of regulation were monitoring, licensing, sanctioning, and arbitration. It concluded by pointing out that regulations are one tool society uses to monitor media practices and content, and that a nation's political structure dictates the course its laws take. As a result, the report suggested revising the Nigerian Broadcasting Code to strengthen the regulatory body's independence and promote industry diversity and healthy competition.